DETERMINATION OF EFFICACY OF ISOXYL, A MYCOLIC ACID INHIBITOR, IN VITRO AGAINST MYCOBACTERIUM.TUBERCULOSIS STRAINS - Vaidya, Shashikant; Punjabi, Kapil; Muley, Shreyasi; Koppikar, Geeta; Kulkarni, Mohan; Chowdhary, Abhay (LIFE: International Journal of Health and Life-Sciences, 2015)
The enzymes involved in the biosynthetic pathways of the critical components including mycolic acids offer attractive and selective targets for the developments of novel anti-mycobacterial agents. Isoxyl (ISO), a mycolic acid inhibitor, is an old drug, which was used for the treatment of tuberculosis was evaluated. Determination of Minimum Inhibitory Concentration (MIC) pattern of clinical isolates of Mycobacterium tuberculosis (M. tuberculosis) to mycolic acid inhibitors namely ISO, Isoniazid (INH) and Ethionamide (ETH) by agar and broth dilution Method was done. Also the Minimum bactericidal concentrations were evaluated. Total 40 MDR and 20 susceptible strains of M tuberculosis were tested. The result of the MIC studies showed that ISO is capable of inhibiting the growth of M. tuberculosis in a range of 1-20μg/ml. Inhibitory activity of ISO was higher than activity of ETH in solid media. Amongst three antituberculosis drugs, INH showed highest bactericidal activity against M. tuberculosis strains followed by ETH. While ISO exhibited lowest bactericidal activity. Amongst, three drugs tested, ISO shows highest MBC/MIC ratio with lowest bactericidal activity. ISO showed significantly lower bactericidal activity against MDR strains than susceptible strains of M. tuberculosis. MBC/ MIC ratio of ISO was similar to MDR and susceptible strains of M. tuberculosis. Overall study implies that ISO may be suitable for the treatment of Tuberculosis, particularly multi-drug resistant kind.